Memengwaawid, to be a butterfly: an Indigenous exploration of Northwestern Ontario Anishinawbe and Muskego or Ininiw sacred stories and teachings in a contemporary novel - Farrell-Morneau, Amy Lynn (2014)
Among their capacities to entertain, to pass down cultural traditions, ceremonies, dances, songs, and to correct undesired behaviours, sacred stories explain how something in nature came to be and how our interactions with those creatures and other life forms around us lead into actions of established ceremonies of respect for the land and ourselves. Thus, from ceremonies and traditions, to codes of conduct and behaviour, to cultural spirituality and beliefs, sacred stories contain the history of Indigenous peoples. With this recorded history in mind, I ask: How are Anishinawbe and Cree sacred story lessons and lessons learned in one's own life journey connected through themes and issues, characters, and Seven Grandfather Teachings morals? With the intention to provide a method of understanding the Seven Grandfather Teachings, I blend the writing of morals into a personally influenced fictional story. I also draw upon theories of Indigenous ways of knowing to bring an understanding of relationships and connections to animals and land into the dissertation story. Concepts of Elders and roles of storytelling, and the oral tradition with connections to self and life are also discussed. I interweave all of these concepts in my theoretical framework into an Indigenous storytelling methodology through the use of an Indigenous story method. To elaborate, I refer to established Indigenous researchers including Jo-Ann Archibald (2008) and Margaret Kovach (2009) to describe how Indigenous storytelling informs and is a research methodology. I also discuss how structures and types of sacred story (Ellis, 1995) can create the foundation of an Indigenous story method. To inform my interpretation of sacred story characters as they appear in the dissertation story, including the characters of Weesquachak and Windigo, I combine the readings from literature in related fields (Indigenous education, Indigenous ways of knowing, Indigenous knowledge) as well as personal understandings gained from in-depth analyses of the sacred story characters. The analysis of sacred story characters includes discussion of character traits, any physical description drawn from sacred story, and actions and behaviours that inform the interpretation of the character and how they appear in the dissertation. This dissertation story is about a 16-year-old girl named Butterfly who, through a series of adventures with selected characters borrowed from sacred story, copes with many different life experiences during a fall semester in high school and learns some of the lessons often found in sacred story and the Seven Grandfather Teachings. A part of my own learning throughout my life and my time during the process of writing this dissertation is built into the dissertation novel: my growing sense of personal and cultural pride, and my strength as an Ojibwe woman.